At 100 Hands: a Collaborative Species Inventory in Sonson and San Francisco (2018)
The research carried out in the municipalities of San Francisco and Sonsón, Antioquia. It begins with the question: "What is this biodiversity of our forests and is it worth conserving?" And it fills the community with power and learning by putting them in a role of researchers in which they participated from the youngest to the oldest. All research brought impressive results for the community raising awareness of the importance of its ecosystem